Microstrip to Parallel-Strip Nonlinear Transition Balun with Stubs and DGS for UWB Dipole Antenna - S. A. Hamzah; S. Mohd Shah; H. Majid; K. N. Ramli; M. S. Zainal; L. Audah; S. Z. Sapuan; A. Ubin; M. Esa; N. N. Nik Abd Malik (Universitas Ahmad Dahlan, 2017)
Three tapered baluns with nonlinear transition are developed for harmonic suppression in dipole antenna. The first balun consists of an exponential profile with the size of a quarter–wavelength for both the height and width with a wideband characteristic. However, for some applications such as narrowband harmonic suppression antennas and wideband-to-narrowband reconfigurable antennas, the suppression of higher operating band is desired. By employing stubs-filter and a defected ground structure (DGS), two narrowband tapered baluns are produced. They are named as an exponential balun-stub and an exponential balun-DGS, respectively, that operate from 1 to 2 GHz. A simulated and measured results that based on the reflection coefficient is found to be better than -10 dB from 1 to 2 GHz. The employment of the stubs and DGS have enabled these baluns to have the capability to reject the unwanted higher frequency band from 2.0 to 10 GHz. Finally, the proposed baluns are employed as a feeding circuit for an ultra wideband (UWB) circular dipole antenna that produces a reasonable outcome.